Antifungal mechanism of cell-free supernatant produced by Trichoderma virens and its efficacy for the control of pear Valsa canker - Zhang, Yang; Lu, Ying; Jin, Zhaoyang; Li, Bo; Wu, Li; He, Yujian (Frontiers in Microbiology, 2024)
Introduction Pear Valsa canker, caused by Valsa pyri (V. pyri), poses a major threat to pear production. We aimed to assess the effectiveness of the cell-free supernatant (CFS) produced by Trichoderma virens (T. virens) to control the development of pear Valsa canker and reveal the inhibitory mechanism against the pathogenic fungi. Results Using morphological characteristics and phylogenetic analysis, the pathogen G1H was identified as V. pyri, and the biocontrol fungus WJ561 was identified as Trichoderma virens. CFS derived from WJ561 exhibited strong inhibition of mycelial growth and was capable of reducing the pathogenicity of V. pyri on pear leaves and twigs. Scanning electron microscopy (SEM) observations revealed deformations and shrinkages in the fungal hyphae treated with CFS. The CFS also destroyed the hyphal membranes leading to the leakage of cellular contents and an increase in the malondialdehyde (MDA) content. Additionally, CFS significantly inhibited the activities of catalase (CAT) and superoxide dismutase (SOD), and downregulated the expression of antioxidant defense-related genes in V. pyri, causing the accumulation of reactive oxygen species (ROS). Artesunate, identified as the main component in CFS by liquid chromatograph-mass spectrometry (LC–MS), exhibited antifungal activity against V. pyri. Conclusion Our findings demonstrate the promising potential of T. virens and its CFS in controlling pear Valsa canker. The primary inhibitory mechanism of CFS involves multiple processes, including membrane damage and negatively affecting enzymatic detoxification pathways, consequently leading to hyphal oxidative damage of V. pyri. This study lays a theoretical foundation for the utilization of T. virens to control V. pyri in practical production.